PENGETAHUAN WIRAUSAHA TERHADAP KINERJA USAHA PADA PENGUSAHA GENERASI Z - Zahra, Fatimah; Franawati, Nadia Fitria; Nufus, Hayatun; Wulan Suci, Ifa Nofika Puspita; Ardiansyah, Tedy; Rizqallah, Muhammad (Universitas Indraprasta PGRI Jakarta, 2024)
Entrepreneurial knowledge plays a crucial role in managing and developing their businesses.. This research is meant to analyze the relationship between entrepreneurial knowledge and business performance. The population in this study is residents of the z generation at 18 to 21 years of age. The sample in this study was divided into two classes of control and experimental classes. As for this study using a quantitative method with an experimental approach. As a result of testing obtained thitung value = 3.46, the value of ttabel = 2.002 of the value is clear that the value t counts 3.46 > ttable = 2.002. Thus, it can be concluded that the h1 was accepted and simultaneously rejected and that